1982
DOI: 10.1007/bf00393726
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and immunohistochemical localization of UDP-glucose: coniferyl alcohol glucosyltransferase in spruce (Picea abies (L.) Karst.) seedlings

Abstract: UDP-glucose: coniferyl alcohol glucosyltransferase was detected in hypocotyls of spruce (Picea abies (L.) Karst.) seedlings. Enzyme activity rose after germination to maximal activity on about the 10th day and then rapidly declined. An antiserum against the glucosyltransferase isolated from cambial sap of spruce (Schmid and Grisebach, 1982, Eur. J. Biochem. 123, 363-370) was employed for localization of the enzyme in cross sections of hypocotyls from 10-d-old spruce seedlings, using the immunofluorescent techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Even though most plant UGTs are predicted to occur in the cytoplasm, experimental evidence is varied. Cell fractionation studies have shown a number of UGTs to be localised to membranes (Loffelhardt and Kopp, 1981;Kalinowska and Wojciechowski, 1987;Warnecke and Heinz, 1994) although several other studies using cell fractionation, immunolocalisation or expression of GFP fusions have reported UGTs in the cytoplasm (Blume et al, 1979;Schmid et al, 1982;Yazaki et al, 1995;Dean et al, 2003;Achnine et al, 2005). The results from both our cell fractionation studies and GFP fusions strongly suggest that UGT85C2, UGT74G1 and UGT76G1 are located in the cytoplasm.…”
Section: Spatial Organisation Of the Steviol Glycoside Biosynthetic Psupporting
confidence: 52%
“…Even though most plant UGTs are predicted to occur in the cytoplasm, experimental evidence is varied. Cell fractionation studies have shown a number of UGTs to be localised to membranes (Loffelhardt and Kopp, 1981;Kalinowska and Wojciechowski, 1987;Warnecke and Heinz, 1994) although several other studies using cell fractionation, immunolocalisation or expression of GFP fusions have reported UGTs in the cytoplasm (Blume et al, 1979;Schmid et al, 1982;Yazaki et al, 1995;Dean et al, 2003;Achnine et al, 2005). The results from both our cell fractionation studies and GFP fusions strongly suggest that UGT85C2, UGT74G1 and UGT76G1 are located in the cytoplasm.…”
Section: Spatial Organisation Of the Steviol Glycoside Biosynthetic Psupporting
confidence: 52%
“…Immunolocalisation has been employed in two instances. Schmid et al (1982) showed a cytosolic localisation of a coniferyl-GT in spruce seedlings, whilst Latchinian-Sadek and Ibrahim (1991) presented evidence of a vesicle-like and cytoplasmic membrane localisation of a¯avonol-B-ring speci®c GT in Chrysoplenium americanum. Ibrahim (1992) subsequently suggested that these results were indicative of a very loose association between the GT and the endoplasmic reticulum.…”
Section: Soup or Structure? ± The Organisation Of Glycosylationmentioning
confidence: 94%
“…Glycosyltransferases are also known to be developmentally regulated (Sparvoli et al 1994;Boss et al 1996;Miller et al 1999;Woo et al 1999;Kita et al 2000) and restricted in tissue localisation (Schmid et al 1982;Vogt and Taylor 1995;Boss et al 1996;Gong et al 1997;Ford and Hùj 1998;Martin et al 1999;Miller et al 1999). …”
Section: Soup or Structure? ± The Organisation Of Glycosylationmentioning
confidence: 98%
“…Previous studies using cellular fractionation or immunolocalization have suggested cytosolic (Anhalt and Weissenböck, 1992; Blume et al. , 1979; Schmid et al. , 1982; Yazaki et al.…”
Section: Properties Of Triterpene Glycosyltransferasesmentioning
confidence: 99%